Removal Rates of NOx, SOx, and Fine Dust Particles in Textile Fabrics Coated with Zeolite and Coconut Shell Activated Carbon - Keun-Hyeok Yang; Ju-Hyun Mun; Jae-Uk Lee (Applied Sciences, 2020)
An effective dipping method for coating of textile fabrics with porous materials is proposed on the basis of the use of epoxy solution consisted of resins, crosslinkers, and dilution solutions. The removal rates of nitrogen oxides (NOx), sulfur oxides (SOx), and fine dust particles in the coated textile fabrics are accessed. The textile fabrics made of polyester are used to effectively reduce fine dust particles through static electricity. Zeolite and coconut shell activated carbon are used as porous material to reduce SOx and NOx, respectively. The effects of the epoxy content and dilution solution types on the SOx removal rate of textile fabrics coated with zeolite are evaluated to determine the optimum coating conditions. In addition, the effects of external environmental conditions, such as washing and freeze thawing, on the SOx and NOx removal rates of the textile fabrics coated with porous materials using the optimum coating conditions are examined. The test results show that the SOx removal rate of textile fabrics coated with zeolite decreases with the increase in the epoxy content. The decrease is 2.9 times larger for textile fabrics coated using deionized water than those coated using isopropyl alcohol. After one wash, the SOx removal rate decreases dramatically. However, the decrease is reduced by 16% when the epoxy content ratio is increased by 0.5%. The effects of washing and freeze thawing on the SOx and NOx removal rates of textile fabrics coated using the deionized water diluted with the epoxy content ratio of 2% are minimal. Consequently, to maintain stable SOx and NOx removal rates under external environmental conditions such as washing and freeze thawing, 98% deionized water dilution and 2% epoxy content ratio are required for the optimum coating of textile fabrics with zeolite and coconut shell activated carbon.